Energy partitioning and controlling factors of evapotranspiration in an alpine meadow in the permafrost region of the Qinghai-Tibet Plateau - Hu, Zhaoyong; Wang, Genxu; Sun, Xiangyang; Huang, Kewei; Song, Chunlin; Li, Yang; Sun, Shouqin; Sun, Juying; Lin, Shan (Journal of Plant Ecology, 2024)
Abstract Energy partitioning and evapotranspiration (ET) of alpine meadows in permafrost areas are crucial for water cycle on the Qinghai-Tibet Plateau. However, seasonal (freeze–thaw cycle) variations in energy partitioning and ET and their driving factors must be clarified. Therefore, 4-year energy fluxes [i.e. latent heat (LE) and sensible heat (H)] were observed, and bulk parameters [i.e. surface conductance, decoupling coefficient (Ω), and Priestley–Taylor coefficient (α)] were estimated in an alpine meadow in the Qinghai-Tibet Plateau. Mean daily LE (27.45 ± 23.89 W/m2) and H (32.51 ± 16.72 W/m2) accounted for 31.71% and 50.14% of available energy, respectively. More available energy was allocated to LE during the rainfall period, while 67.54 ± 28.44% was allocated to H during the frozen period. H was half the LE during rainfall period and seven times the LE during frozen period due to low soil water content and vegetation coverage during the frozen season. Mean annual ET was 347.34 ± 8.39 mm/year, close to mean annual precipitation. Low mean daily Ω (0.45 ± 0.23) and α (0.60 ± 0.29) throughout the year suggested that ET in the alpine meadow was limited by water availability. However, ET was constrained by available energy because of sufficient water supply from precipitation during rainfall season. In contrast, large differences between ET and precipitation indicated that soil water was supplied via lateral flow from melting upstream glaciers and snow during the transition season. The results suggest that seasonal variations in bulk parameters should be considered when simulating water and energy fluxes in permafrost regions.